Preventing corruption by promoting trust: Insights from behavioral science - Johann Graf Lambsdorff (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2015)
Governments, companies and organizations across the world have implemented strategies for countering corruption. A growing body of so-called best practice has emerged in the last 20 years. But some approaches have been criticized for being costly, ineffective or even counterproductive. This study illustrates this, using six examples, relating to the four-eyes principle, procurement, development aid, compliance statements, leniency and the tone at the top. Increasingly, behavioral science has provided insights on how to improve policies. These insights, along with experimental evidence, are applied to the six examples to provide direction to behaviorally better informed policies.
Keywords: 330